Histological and histomorphometric studies of the effects of hyaluronic acid on osseointegration of titanium implant in rabbits - Mohammad, Mohammad H.; Al Ghaban, Nada M.H. (Journal of Baghdad College of Dentistry, 2018)
Background: One of the unique prosthesis for tooth or teeth replacement is the dental implant. Our attempt is using a biomaterial system that is easily obtained and applicable and has the ability to provoke osteoinductive growth factor to enhance bone formation at the site of application. One of these natural polymers is hyaluronic acid. Material and methods: Sixty machined surface implants from commercially pure titanium rod inserted in thirty NewZealand rabbits. Two implants placed in both tibia of each rabbit. The animals scarified at 1, 2 and 4 weeks after implantation (10 rabbits for each interval). For all of animals the right tibia’s implant was control (uncoated) and the left one was experimental (coated with 0.1ml Hyaluronic acid gel). All sections have been stained with Haematoxylin and Eosin then they were histologically examined and assessed for histomorphometric analysis for counting of bone cells (osteoblast, osteocyte and osteoclast), cortical bone thickness, trabecular width, thread width and marrow space star volume (V*). Results: Histological findings for hyaluronic acid- coated titanium implant revealed an earlier bone formation, mineralization and maturation than that in control groups. Histomorphometric analysis for all bone parameters that examined in this study, showed highly significant difference between control and experimental groups in all healing intervals. Conclusion: Commercially pure titanium endosseous implants coated with hyaluronic acid may be osteocoductive thus accelerating healing process and enhancing osseointegration.